Trend change of transmission route of COVID-19-related symptoms in Japan (2020)
Objectives The Japanese prime minister declared a state of emergency on April 7 to combat the outbreak of coronavirus disease 2019 (COVID-19). This declaration was unique in the sense that it was essentially driven by the voluntary restraint of the residents. We examined the change of infection route by investigating contact experiences with COVID-19-positive cases. Study design This study is a population-level questionnaire-based study using a social networking service (SNS). Methods To assess the impact of the declaration, this study used population-level questionnaire data collected from an SNS with 121,375 respondents (between March 27 and May 5) to assess the change in transmission routes over the study period, which was measured by investigating the association between COVID-19-related symptoms and (self-reported) contact with COVID-19-infected individuals. Results The results of this study show that the declaration prevented infections in the workplace, but increased domestic infections as people stayed at home. However, after April 24, workplace infections started to increase again, driven by the increase in community-acquired infections. Conclusions While careful interpretation is necessary because our data is self-reported from voluntary SNS users, these findings indicate the impact of the declaration on the change in transmission routes of COVID-19 over time in Japan.